Un entretien avec Diane Labrosse - Cornell, Andrea-Jane (Intersections: Canadian Journal of Music / Intersections : revue canadienne de musique, 2006)
This interview with Diane Labrosse was conducted in December 2004 in the offices of Production SuperMusique within the framework of Dr. Andra McCartney's In and Out Of the Sound Studio project. Andrea Jane Cornell asked Labrosse about the experiences that brought her to choose sound as a medium for her artistic expression, and the methods that she employs to create sound.